Navigating the National Geographic Standards in the Philippine Social Studies Curriculum - Tyrone Gil; Ryan Destura (Universitas Muhammadiyah Kuningan, 2022)
The social studies discipline as a multidisciplinary and integrative curriculum includes geographic literacy and spatial thinking as part of its academic nature in developing young learners to become an informed and reasoned decision-makers in participating in a culturally diverse, democratic, and interdependent society. Geography education has an anticipated space at the heart of the social studies curriculum next to history. In a social studies classroom, geographical skills and knowledge have been used to interpret the past and analyze the future. This exploration navigated and evaluated the alignment of the social studies curriculum standards and competencies to the National Geographic Standards of the NCGE and explored the common teaching approaches in facilitating geographic education in the basic education curriculum. Using qualitative content analysis, the researcher examined the curriculum guide as the main document supplemented with the learner’s module and teacher’s guide. The findings revealed significant curriculum alignment and learner-centered teaching approaches in geography education.